2021
DOI: 10.1002/jdd.12817
|View full text |Cite
|
Sign up to set email alerts
|

A unique and effective method of anatomy education: Small‐group learning with prosected plastinated specimens

Abstract: Objective At the New York University College of Dentistry, we are faced with the challenge of teaching Head and Neck Anatomy to a class of approximately 380 first‐year students. We have developed an innovative anatomy curriculum that has proven effective in facilitating students’ learning and long‐term retention of the material. It has the added benefit of being time‐ and cost‐efficient. Here, we share the structure of our curriculum and examine the student outcomes and student feedback. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Additional feedback noted the time saved was largely a result of not having to remove "fat" and "fascia," as these tissues are largely not emphasized on practical exams and therefore perceived as unimportant. The usefulness of prosection specific to student time efficiency, decreased cost and resources, and peer teaching has been well established, 5,[18][19][20][21] and feedback from our prosection cohort is consistent with these previously reported advantages.…”
Section: Analysis Of Student Perceptions From Prosection Cohortsupporting
confidence: 87%
“…Additional feedback noted the time saved was largely a result of not having to remove "fat" and "fascia," as these tissues are largely not emphasized on practical exams and therefore perceived as unimportant. The usefulness of prosection specific to student time efficiency, decreased cost and resources, and peer teaching has been well established, 5,[18][19][20][21] and feedback from our prosection cohort is consistent with these previously reported advantages.…”
Section: Analysis Of Student Perceptions From Prosection Cohortsupporting
confidence: 87%
“…Previous research has also concluded that learning is more durable when self-testing is spaced out over time than when it is massed together, a technique called spaced repetition. [18][19][20][21][22][23] Although massed learning such as cramming for exams improves short-term memory, not much of the information remains recallable over time. If study efforts are spaced out, however, long-term retention is improved.…”
Section: Introductionmentioning
confidence: 99%
“…Bjork 14 stated that while self‐testing might slow down the initial learning process, it can produce beneficial long‐term outcomes when compared with restudying the material. Previous research has also concluded that learning is more durable when self‐testing is spaced out over time than when it is massed together, a technique called spaced repetition 18–23 . Although massed learning such as cramming for exams improves short‐term memory, not much of the information remains recallable over time.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the above, plastination seems to be a suitable alternative method for teaching anatomy and related disciplines, [40][41][42] given its cost-effectiveness. 43 Such technology also allows producing long-term and non-toxic final specimens (clean and odorless), 31,44 thus preserving anatomic structure and variance.…”
mentioning
confidence: 99%